(untitled) (REMUNOM, 2026)
This study analyzes teacher training in relation to neurodevelopmental disorders, with an emphasis on the pedagogical strategies necessary to promote inclusive and equitable education. This is a qualitative study, developed through a literature review, covering scientific publications between 2020 and 2025 in recognized databases, such as SciELO, Google Scholar, and the CAPES Journal Portal. The analysis shows that, although normative and discursive advances in school inclusion are significant, weaknesses still persist in the initial and continuing training of teachers, especially with regard to understanding neurodevelopmental disorders and applying effective pedagogical practices. The results indicate that the lack of specific preparation compromises the implementation of inclusive practices and reinforces inequalities in the educational process. It is concluded that strengthening teacher training, combined with institutional support and interdisciplinary action, is a central element in the construction of pedagogical practices capable of responding to the demands of school diversity, contributing to the consolidation of a truly inclusive education.